Transitioning to Good Health and Well-Being - Flahault, Antoine (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Transitioning to Good Health and Well-Being addresses critical issues of health in the context of sustainability, which need to be tackled in order to achieve Agenda 2030. Acknowledging the dramatic improvements that have been made in the past decades with regards to health, we also face disparities that remain amongst and within countries. While life expectancy has more than doubled, we are, at the same time, confronted with the challenges that come along with population growth alongside environmental change, migration, ageing, and economic disparities. In its 2018 progress report concerning SDG 3, the UN stated that, while the quality of global health is increasing, "people are still suffering needlessly from preventable diseases", both infectious and non-communicable, "and too many are dying prematurely". Although we are on the verge of eradicating, poliomyelitis, which disables 350'000 children each year, we continue to have few answers for outbreaks of emerging infectious diseases. Making progress against these outbreaks with strong health systems, particularly in neglected or inaccessible regions, is deeply connected to further issues targeted by the UN SDGs such as (restricted) access to clean water, healthy food, or continuing political instabilities as well as gender inequalities. Transitioning to Good Health and Well-Being, therefore, offers a vessel for a productive reflection and conversation on the meaning of and possibilities for global health, giving voice to a range of scholars, strategists and practitioners. Transitioning to Good Health and Well-Being is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. The book series is intended to reach beyond disciplinary, even academic boundaries.